Model of intellectual information system of definition of structures, characteristics and concrete properties - Михеев, Иван Андреевич (Eastern-European Journal of Enterprise Technologies, 2010)
The conceptual model of the intellectual information system for the decision of basic tasks of concrete technology is resulted. Functional-organizational architecture of information technology «Concrete» is described.